Influence of chlorinated paraffin on properties of silica filled polychloroprene - P. Sae-oui (2018)
Roles of the two widely used chlorinated paraffins, namely Cereclor S45 and Cereclor 48, in properties of silica filled polychloroprene were investigated. The results reveal that chlorinated paraffin significantly improves the processability. The improvement is more pronounced for Cereclor S45 due to its lower viscosity. However, the addition of chlorinated paraffin has a negative effect on cure. Owing to the reduction of crosslink density and the plasticising effect of chlorinated paraffin, several mechanical properties are impaired, e.g. tensile strength, modulus, hardness, abrasion resistance as well as rebound resilience. However, the deterioration of both tensile strength and modulus is not pronounced at low loading of chlorinated paraffin (≤8.0 parts per hundred of rubber, phr). Although chlorinated paraffin has little influence on the relative tensile strength, the relative 100% modulus is affected to a greater extent due to the combination of post curing retardation and evaporation of chlorinated paraffin during thermal aging. © Institute of Materials, Minerals and Mining 2009.